Soborno transnacional : beneficios por colaboración y principio de oportunidad : la necesidad de coordinación entre la sanción penal y las sanciones administrativas (2020)
Colombia has established a dual system of sanctioning consequences from transnational bribery behavior. In first place there are administrative consequences from the Superintendence of Corporations and secondly criminal consequences for the crime of transnational bribery. Law 1778 of 2016 established a benefits for collaboration program (clemency program) under which the Superintendence of Companies has the power to grant benefits to those who participate in transnational bribery conducts as long as they confess it to the Superintendency and collaborate in a timely manner with the delivery of information and evidence related to said conduct. 3 Within the framework of these faculties, both systems share a series of competencies that require effective coordination that allow to meet the State's objectives and to ensure that incentives are adequate to promote the elimination of this type of conduct which is harmful to the economy. In this paper we try to analyze what those moments of collaboration should be between the system of penal consequences and administrative consequences that guarantee an adequate functioning of the legal system in the fight against transnational bribery.